(1+2/3 – 1/4) (0,8 – 3/4)^2 (-7/13 + 3/5) : 3/11 + ( -6/3 + 2/5) : 3/11

(1+2/3 – 1/4) (0,8 – 3/4)^2
(-7/13 + 3/5) : 3/11 + ( -6/3 + 2/5) : 3/11

1 bình luận về “(1+2/3 – 1/4) (0,8 – 3/4)^2 (-7/13 + 3/5) : 3/11 + ( -6/3 + 2/5) : 3/11”

  1. Giải đáp+Lời giải và giải thích chi tiết:
    (1+2/3 -1/4 )(0,8-3/4)^2
    =(5/3-1/4)(1/20)^2
    =17/12 . 1/400
    =17/4800
    _____________________________
    (-7/13 +3/5):3/11+(-6/3 +2/5) :3/11
    =[(-7/13+3/5)+(-6/3+2/5)]:3/11
    =[-7/13+3/5-6/3+2/5]:3/11
    =[(-7/13 -6/3)-(3/5+2/5)]:3/11
    =[-1 – 1]:3/11
    =-2 : 3/11
    =-22/3
     
     

    Trả lời

Viết một bình luận

Câu hỏi mới